SPATIAL DISTRIBUTION ANALYSIS OF FIELD BATHYMETRY AND LANDSAT 8 SATELLITE IMAGERY ON THE FISH POTS CATCH IN JEPARA REGENCY - Zulyani Zulyani; Agus Hartoko; Herry Boesono (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2021)
Pots operated are traping fishes and passived, making the fish easier to get in and difficult to escape. Problems faced fisherman is difficulty finding ideal fishing grounds. This study to analyze real bathymetry spatial distribution and Satellite Imagery Landsat 8 with operationing of pots in Jepara. This study uses the methods purposive sampling with primary data is real bathymetry, and fish measures from pots catching. Secondary data is tides local and satellite imagery Landsat 8. Result of polynomial regression Landsat 8 bathymetry to real bathymetry is 25.88%, whereas the Landsat 8 bathymetry against long size of fish catched is only 5% and 3.3% bathymetry was able to explain the fish weight variables. On real bathymetry with long size of fish is only 3.6% define long size variables and 1.6% for weight variables. Hypothesis is tested with linear regression in SPSS 22. Test results assumed spatial distribution of bathymetry had no effect on the catch of pots. Based on a simple linear regression test, the effect values is only 0.9 % while on fish weight there was no effect at all. Results of real bathymetry analysis with satellite image Landsat 8 have a relationship with a coefficient of determination value is 0.258).